Manipulative messages in the headlines of media sources - Голота, Тарас Сергійович (Київський національний університет імені Тараса Шевченка, 2023)
In this article, the author analyzes headlines on digital platforms of media sources, paying special attention to the manipulative content of the delivered messages. The research is based on the material of three websites, the authors of which manipulate the emotions of the recipients while providing information – “Tarasova Pravda“, “Naspravdi.Today”, and “Politeka”. The basic aspects of suggestive influence and manipulation of information during the speech act are defined and explained. In today’s rapidly evolving digital landscape, understanding the linguistic mechanisms of manipulation and suggestion in written texts is becoming increasingly crucial. This study not only sheds light on the deceptive methods employed in the headlines of Ukrainian-language online media resources but also highlights the importance of fostering media literacy among consumers. By enhancing awareness of manipulative tactics and promoting critical thinking skills, individuals will be better equipped to discern fact from fiction, ultimately contributing to a more well-informed society. The advancement and proliferation of cutting-edge information and communication technologies have led to an escalation in dissemination of manipulative texts. It can be posited that suggestion operates as a crucial instrument of verbal manipulation in written materials. Consequently, our investigation primarily focuses on examining manipulative texts (specifically, headlines within the context of this article) concerning their suggestive component. The research vectors for this issue encompass the linguistic analysis of manipulative texts for categorization purposes, recognition of suggestion components, exploration of linguistic methods employed for disinformation, and countermeasures against verbal manipulation. The objective of this article is to scrutinize the headlines of news articles featured on Ukrainian-language online media resources (based on materials from three websites: “Tarasova Pravda”, “Naspravdi.Today”, and “Politeka”), as well as to detect, classify, and interpret linguistic techniques of manipulation and suggestion used in messages, excluding the proportion of manipulative content. The conducted linguistic analysis based on the 100 headlines gives reason to claim that 66.67 % of the article headlines in the three news web portals we have investigated contain messages aimed at manipulating emotions – “Tarasova Pravda” (33.33 %), “Naspravdi.Today” (76.67 %), and “Politeka” (90 %).

Автор аналізує заголовки на цифрових платформах медіаресурсів, надаючи особливу увагу маніпулятивному змісту повідомлень. Дослідження базоване на матеріалі 3-х веб-сайтів, автори яких маніпулюють емоціями реципієнтів у перебігу подання інформації – “Тарасова правда”, “Naspravdi.Today” та “Politeka”. Подано дефініцію й розтлумачено базові аспекти сугестивного впливу і маніпуляції інформацією впродовж мовленнєвого акту. Проведений лінгвістичний аналіз на основі 100 заголовків дає підстави стверджувати, що 66.67 % заголовків статей у 3-х досліджених нами новинних веб-портали містять повідомлення, орієнтовані на маніпуляцію емоціями – “Тарасова правда” (33.33 %), “Naspravdi.Today” (76.67 %) та “Politeka” (90 %).
Маніпулятивні повідомлення в заголовках новинних інтернет-ресурсів
Keywords: маніпулятивний текст; маніпулятивний заголовок; маніпулятивне повідомлення; маніпуляція емоціями; сугестія та її прийоми; дезінформація в медіа; manipulative text; manipulative headline; manipulative message; manipulation of emotions; suggestion and its techniques; disinformation in the media